Does smoking cessation with varenicline worsen vascular endothelial function?. Issue 6 (21st June 2013) - Umeda, Akira; Kato, Toru; Yamane, Tateki; Yano, Heiichi; Ieiri, Tamio; Miyagawa, Kazuya; Takeda, Hiroshi; Okada, Yasumasa
Abstract : Objectives: A meta-analysis suggested that the use of varenicline, which is a partial agonist of nicotinic acetylcholine receptors and is effective in smoking cessation, increases the risk of cardiovascular events within 52 weeks of starting treatment. Defining these events as occurring during drug treatment (usually for 12 weeks) or within 30 days of discontinuation, another meta-analysis showed that the risk was statistically insignificant. In the present study, we aimed to clarify the effect of varenicline-assisted smoking cessation on vascular endothelial function assessed by flow-mediated vasodilation (FMD). Design: Before–after and time-series. Setting: Tochigi Prefecture, Japan. Participants: Data of 85 participants who visited nicotine-dependent outpatient services were reviewed. FMD was repeatedly measured in 33 of the 85 participants. Inclusion criteria: 20 years and older, Brinkman index ≥200, Tobacco Dependence Screener ≥5 and stated motivation to quit smoking. Interventions: Each participant was treated with varenicline titrated up to 1.0 mg twice daily (for 12 weeks in total). Primary and secondary outcome measures: Participants were evaluated by FMD prior to, and 3 months after, complete smoking cessation. Follow-up FMD measurements were carried out every 3 months if possible. Changes in FMD during varenicline use were also evaluated. Results: FMD was significantly increased from 4.0±1.8% to 5.5±2.2% (p<0.01, n=22) 3 months after complete cessation. Although the timecourse of FMD in most of the cases showed an increase with fluctuations, there was an exceptional case where FMD decreased over the 9 months following complete cessation. Although statistically insignificant, FMD also increased during varenicline use (from 3.7±2.7% to 4.3±2.8%, n=11). Conclusions: Our observations suggest that in ceasing smokers, varenicline and smoking cessation do not lead to a worsening of the vascular endothelial function. Trial registration: FK-79 (International University of Health and Welfare).